STUDIO-BASED LEARNING IN HIGHER EDUCATION: A SYSTEMATIC REVIEW OF PEDAGOGICAL APPROACHES IN ART AND DESIGN - Zainuddin, Nasaie; Zakaria, Muhammad Hisyam; Aris, Asliza (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This systematic analysis summarises the results of 42 peer-reviewed papers that were published between 2000 and 2025 and looks at modern pedagogical approaches in studio-based learning (SBL) in higher education art and design programs. Through iterative creation, critique, and reflection, SBL which is based on constructivist and experiential learning theories promotes creativity, critical thinking, and cooperative problem-solving. Five major topics emerge from the analysis: (1) SBL’s instructional features; (2) digital technology integration; (3) multidisciplinary collaboration; (4) inclusivity and learner diversity; and (5) ongoing implementation issues. The results show that while interdisciplinary initiatives improve relevance and employability, digital tools, blended studios, and AI-enhanced methods increase flexibility and global connectivity. But there are still issues like scarce resources, difficult evaluation of creative outputs, institutional restrictions on exploratory learning, and disparities in inclusivity. The review emphasises the necessity for flexible, culturally sensitive, and long-lasting SBL models that strike a balance between the embodied, social, and creative aspects of traditional studio culture and technology innovation. To make sure SBL stays inclusive, future-ready, and in line with changing expectations from the creative industry, recommendations include funding for infrastructure, curriculum change, and educator training.